Container characteristics and dengue hemorrhagic fever incidence - Wanti Wanti; Ririh Yudhastuti; Hari Basuki Notobroto; Sri Subekti; Agustina Agustina; Christine Ekawati (International Journal of Public Health Science (IJPHS), 2019)
The condition of Kupang City has low rainfall, low rainy days and includes dry areas, but it turns out that Kupang City had always the highest incidence rate in Nusa Tenggara Timur Province and exceed the national average. This study will analyze the relationship of container characteristic to the incidence of DHF in Kupang City. This study was an observational analytic study with a case control design. The study conducted in 25 villages with total sample 500 people of DHF patients and non DHF patients in Kupang City. The research variables are number of container, water height, water volume, water pH, container type, container location, container material, container lid, and container color which were collected by doing direct observation and measuring the object of study. The collected data was processed and analyzed statistically using Independent T test and Chi Square test. The container conditions related to the incidence of DHF were the amount of container, water pH, and type of container. Whereas the container conditions that were not related to the incidence of DHF are water level, water volume, container location, container material, container cover and container color.